2019
DOI: 10.3390/jrfm12030106
|View full text |Cite
|
Sign up to set email alerts
|

Bank Competition, Foreign Bank Entry, and Risk-Taking Behavior: Cross Country Evidence

Abstract: This unique study examines the interactive role of bank competition and foreign bank entry in explaining the risk-taking of banks over the globe. We used cross-country data for the banking sector from 2000 to 2016. Using the pooled regression model and Two-stage Least Squares model (2SLS with Generalized Method of Moments GMM), we document that foreign bank entry decreases the risk-taking behavior of the banks to a certain level and exhibits an inverted U-shaped relation with financial stability. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 71 publications
1
18
1
2
Order By: Relevance
“…Some prior studies found that banks located in countries with higher banking sector development have lower percentage of non-performing loans and are less risky (Laeven & Levine 2009;Srairi 2013). On the other hand, Chen et al (2019) observed that banking sector development increases insolvency risk and credit risk in a cross-country study.…”
Section: Definitions Of Variablesmentioning
confidence: 80%
“…Some prior studies found that banks located in countries with higher banking sector development have lower percentage of non-performing loans and are less risky (Laeven & Levine 2009;Srairi 2013). On the other hand, Chen et al (2019) observed that banking sector development increases insolvency risk and credit risk in a cross-country study.…”
Section: Definitions Of Variablesmentioning
confidence: 80%
“…From the perspective of Claessens and Laeven (2004), the entry of foreign banks enhances the competitiveness of banking systems. Although, at other times, foreign banks may also induce undue competition (Chen et al , 2019), which increases financial fragility (Wu et al , 2017), the penetration of foreign banks appears to have led to a less competitive banking industry in Latin America (Yeyati and Micco, 2007). Foreign banks are a precondition for improved efficiency of the banking system of developing economies (Ghosh, 2016) and deregulated environment (Sturm and Williams, 2004).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In the second phase, the bank managers use the first phase intermediate outputs to create suitable outputs of loans and securities investments and an undesirable output of non-performing credits (Fukuyama & Weber, 2015). Chen et al (2019) concluded that capital regulation stringency and restriction on bank's activities can reduce the risk factor level successfully. This also applies to the policy implication for foreign investors and regulatory authorities.…”
Section: Hypothesis Developmentmentioning
confidence: 99%